Evidence-based psychotherapies II: changes in models of treatment and treatment delivery. (March 2015) - Kazdin, Alan E
Decades of psychotherapy research have yielded a few hundred interventions with strong evidence on their behalf. In the prior companion article, methodological and substantive concerns were raised in relation to what we can say about evidence-based psychotherapies and their impact. Among the methodological concerns are the control conditions to which evidence-based psychotherapies are compared, selective reporting of measures, and the paucity of evidence that evidence-based psychotherapies have clinically significant impact. Among the substantive concerns are limited findings to help direct patients to treatments from which they are likely to profit and to understand the mechanisms responsible for therapeutic change. In this article, two shifts in evidence-based psychotherapy research are highlighted to convey novel and needed directions to augment the impact of treatment and the scale on which it can be delivered. First, transdiagnosis and transtreatment are discussed as a departure from traditional evidence-based psychotherapy research by emphasizing interventions that can be applied across multiple domains. Common biological, psychological, and environmental underpinnings of many disorders and select treatments showing reliable changes across multiple problems are altering evidence-based psychotherapy research. Second, novel models of treatment delivery have emerged from global health care, business, economics, and the media, and are well outside of mainstream mental health professions. Two models (task shifting and best-buy interventions) illustrate how different ways of delivering treatment are essential to reach large and diverse swaths of unserved individuals and have impact on the burden of mental illness.